Helping as a Concurrent Activity: How Students Engage in Small Groups While Pursuing Classroom Tasks - Wakke, Denise; Heller, Vivien (Frontiers in Psychology, 2022)
This study examines interactions in which students help each other with their learning during classroom instruction, forming groups in the process. From a conversation analytic perspective, helping is assumed to be a sequentially organized activity jointly accomplished by the participants. As an activity that proceeds alongside other ongoing classroom activities, helping can be conceived as part of a multiactivity that poses students with multi-faceted interactional and moral challenges. While previous research on helping in educational contexts has primarily focused on the influence of helping on learning outcomes and social dynamics in helping interactions, the present study investigates how students cope with the intricacies of moral commitments inherent in helping as a concurrent activity. The aim of this paper is two-fold. First, we aim to elaborate on how students’ dual involvements – i.e., their involvement in classroom activities while simultaneously providing help – manifest in the ways in which groups are constituted, maintained, and dissolved. The analyses reveal that the problem definition is a key moment in the sequential and bodily-spatial unfolding of the help interaction, inducing different arrangements that constitute a continuum, at each end of which there is a dominant orientation towards the shared space of helping or towards the individual/collective space. Furthermore, from a methodological perspective, our study aims to demonstrate the extent to which multimodal interaction analysis is applicable when examining naturally occurring groups; in this case, in interactive processes of helping. The study is based on a data corpus that comprises video recordings of mathematics and German lessons from two fifth-grade classrooms.